Attitude of Para-veterinarians towards Training (Indian Journal of Extension Education, 2016)
Attitude of para-veterinarians towards training and extent of relationship between the socio- psychological profile and attitude was assessed by ex-post- facto research design method in Nalgonda district of erstwhile Andhra Pradesh (presently in Telangana state). Majority of the para-veterinarians belonged to middle age group , intermediate to graduation level of education , medium experience and received medium duration of training. Majority of them had medium guidance and supervision,mass media exposure,innovativeness, risk preference, rational decision making ability,achievement motivation,job satisfaction,scientific orientation and were having medium attitude followed by high and low attitude towards training. Except age and experience remaining ten variables i.e innovativeness, risk preference, rational decision making ability and achievement motivation had positive and significant relationship with attitude of para-veterinarians towards training. It is attributed that future training activity must be preceded by a realistic assessment of training needs and also require attitudinal enhancement.